Potential Efficacy of Erythropoietin on Reducing the Risk of Mortality in Patients with Traumatic Brain Injury: A Systematic Review and Meta-Analysis. (29th October 2020) - Liu, Chengli; Huang, Changsheng; Xie, Jie; Li, Hui; Hong, Michael; Chen, Xuemei; Wang, Junmin; Wang, Jiarui; Li, Zhanfei; Wang, Jian; Wang, Wei
Abstract : Objective . The objective of this study is to assess the effectiveness of erythropoietin (EPO) on mortality, neurological outcomes, and adverse event in the treatment of traumatic brain injury (TBI). Methods . We searched databases including PubMed, OVID, and the Cochrane Library from inception until October 18, 2019 for randomized controlled trials (RCTs) to compare EPO treatment group and placebo in patients with TBI. Two authors independently processed the data and evaluated the quality of inclusion studies. Statistical analysis was performed with heterogeneity test with I 2 and chi-square tests. We summarized the mortality, prognosis of neurological function, and deep vein thrombosis (DVT) outcomes and presented as risk ratio (RR) or risk difference (RD) with a 95% CI. Results . Seven RCTs accounting for 1180 patients were included after meeting the inclusion criteria. Compared with placebo, the overall mortality of EPO-treated patients was significantly reduced (RR 0.68 [95% CI 0.50-0.93]; p = 0.02 ). EPO therapy did not improve neurological prognosis (RR 1.21 [95% CI 0.93-1.15]; p = 0.16 ) or increase the occurrence of DVT (RR 0.83 [95% CI 0.61–1.13]; p = 0.242 ), which showed no significant difference. Conclusions . The results showed that the administration of EPO may reduce the risk of mortality without enhancing the occurrence of DVT in TBI patients. However, the effect of EPO on neurological outcome remains indistinct. Through subgroup analysis, we demonstrated that the dose of EPO may be a potential factor affecting the heterogeneity in neurological function and that the follow-up duration may influence the stability of the result.